Creating Visionaries Through Positive Leadership: Shifting Educational Paradigms Towards Strengths - Dockrill Garrett, Melissa (Canadian Journal of Educational Administration and Policy / Revue canadienne en administration et politique de l’éducation)

(untitled) (Department of Educational Administration, University of Saskatchewan, 2023)
Elements of strength-based pedagogy are evident in current practices being implemented in Canadian schools as well as internationally. Classroom teachers appreciate the importance of creating a positive learning environment for students where the latter feel a sense of belonging, choice, and self-efficacy toward their learning (Deci & Ryan, 2008; Rickabaugh, 2016). While many educators apply such practices at the classroom level, strength-focused pedagogies can be organized through the conceptualization of a unifying framework. Building on research which proposed a dual-dimensional approach to student support services, this article explores the role of school leadership in shifting a school’s culture toward one that values, identifies, and leverages the strengths of students and educators to promote flourishing within their schools. Employing an Appreciative Inquiry action research design (Cooperrider et al., 2000; Stowell, 2012) to engage research participants, this study used Keyes’ (2002) dual-dimensional model as a lens through which to investigate the application of strength-based concepts and practices within school and classroom settings.An Appreciative Inquiry (AI) Action Research Design (Stowell, 2012; Cooperrider et al., 2000) was used to engage research participants, using Keyes’ dual-dimensional model (Keyes, 2002) as a lens through which to investigate the use of strength-based concepts and practices within school and classroom settings.